2002
DOI: 10.1139/f02-104
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reduced pH on chemical alarm signalling in ostariophysan fishes

Abstract: Under laboratory conditions, we examined the effects of acute exposure to weakly acidic conditions (pH 6.0) on the ability of fathead minnows (Pimephales promelas) and finescale dace (Phoxinus neogaeus) to detect and respond to conspecific and artificial alarm pheromones. Initially, minnows and dace exhibited normal antipredator responses when exposed to conspecific alarm pheromones under normal (pH 8.0) conditions. When retested at pH 6.0, we observed no significant antipredator response. However, when return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 27 publications
5
74
0
Order By: Relevance
“…Recently, a very similar range of behavioural changes has been observed in experiments with marine fish exposed to predicted future changes in ocean pH due to rising atmospheric CO 2 [39,40]. However, despite the remarkable similarity in many of the behavioural responses, the underlying mechanisms appear to be entirely different [37,41]. In this review, we compare and contrast the effects of acidification on olfactory-mediated behaviour in freshwater and marine organisms and present evidence for significant dissimilarities between the underlying mechanisms of action.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, a very similar range of behavioural changes has been observed in experiments with marine fish exposed to predicted future changes in ocean pH due to rising atmospheric CO 2 [39,40]. However, despite the remarkable similarity in many of the behavioural responses, the underlying mechanisms appear to be entirely different [37,41]. In this review, we compare and contrast the effects of acidification on olfactory-mediated behaviour in freshwater and marine organisms and present evidence for significant dissimilarities between the underlying mechanisms of action.…”
Section: Introductionmentioning
confidence: 79%
“…Exposure to alarm cues can elicit adaptive predator avoidance behaviour, such as reduced activity levels and increased hiding or tighter group cohesion [43]. These behavioural responses to alarm cues have been observed in a range of freshwater fishes, including fathead minnows (Pimephales promelas), finescale dace (Phoxinus neogaeus), pumpkinseed (Lepomis gibbosus) and rainbow trout (Oncorhynchus mykiss) [20,37,44]. However, predator avoidance behaviour was diminished or absent when these alarm cues were presented in experimental treatments acidified using a minute amount of sulfuric acid (often a major contributor to freshwater acidification) [20,38,45].…”
Section: Ecological Effects Of Acidification On Olfaction (A) Freshwamentioning
confidence: 99%
“…For instance, information disruption has been shown to impair alarm responses in several fishes exposed to acidified waters [37,38]. Laboratory evidence suggests that an alarm pheromone of these fishes suffers an irreversible change in structure that renders it non-functional [39]. This particular effect occurs completely external to the impaired organism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acquired recognition of novel predators (a covert response to alarm cues; Smith 1999) likewise leads to increased survival during encounters with predators Chivers 2000, 2001b;Gazdewich and Chivers 2002). Brown et al (2002) have demonstrated that the ability of two cyprinid species (fathead minnows, Pimephales promelas and finescale dace, Phoxinus neogaeus) to detect and respond to conspecific and artificial alarm pheromones is significantly impaired under weakly acidic conditions (pH 6.0). When exposed to conspecific skin extract or hypoxanthine-3-N-oxide (H3NO), the putative Ostariophysan alarm 'pheromone', (Brown et al 2000(Brown et al , 2002 under natural (pH 7.8) conditions, both minnows and dace exhibited significant increases in antipredator behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al (2002) have demonstrated that the ability of two cyprinid species (fathead minnows, Pimephales promelas and finescale dace, Phoxinus neogaeus) to detect and respond to conspecific and artificial alarm pheromones is significantly impaired under weakly acidic conditions (pH 6.0). When exposed to conspecific skin extract or hypoxanthine-3-N-oxide (H3NO), the putative Ostariophysan alarm 'pheromone', (Brown et al 2000(Brown et al , 2002 under natural (pH 7.8) conditions, both minnows and dace exhibited significant increases in antipredator behaviour. When acclimated to weakly acidic conditions (pH 6.0) over 4 days and retested, there was no significant response to natural or artificial alarm cues.…”
Section: Introductionmentioning
confidence: 99%